(untitled) (Bangladesh Journal of Plant Taxonomy, 2009)
Pollen morphology of two subfamilies of Ericaceae, Cassiopoideae and Harrimanelloideae, was studied using light microscopy (LM), scanning electron microscopy (SEM), and also, for selected species, transmission electron microscopy (TEM). The systematic significance of new palynological data is discussed in the light of the recent classification of Ericaceae. The Cassiopoideae are stenopalynous; the four 3-aperturate grains are united in compact minute tetrads with striate apoclopial exine sculpture. Infra- and inter-specific variations have been observed in some palynological features of Cassiope, this might be due to geographical distribution. The Harrimanelloideae pollen grain is characterized by minute tetrahedral tetrads with coarsely rugulate to psilate apoclopial exine sculpture and perforated septum. Pollen morphology supports the subfamilial status of Cassiopoideae and Harrimanelloideae, and the close relationship between the members of subfamily Harrimanelloideae and Vaccinioideae. The secondary sculpture on the exine surface might be a synapomorphic palynological character state for Harrimanelloideae + Styphelioideae + Vaccinioideae clade. Keywords: Pollen morphology; Systematics; Cassiopoideae; Harrimanelloideae; Ericaceae. DOI: 10.3329/bjpt.v16i1.2745 Bangladesh J. Plant Taxon. 16(1): 37-46, 2009 (June)